Ginger Cultivation and Its Antimicrobial and Pharmacological Potentials 2020
DOI: 10.5772/intechopen.88899
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Antidiabetic Activities of Ginger

Abstract: Diabetes mellitus, a chronic metabolic disorder with major health care burden worldwide, is increasing, with 173 million adults being diabetic and over 8 million deaths recorded annually. Undesirable pathological conditions and high rates of secondary failure limit the use of current antidiabetic agents, thus, the need for more effective antidiabetic agents. Medicinal plants such as spices, rich in bioactive components that promote prevention and treatment of chronic conditions such as heart disease, cancer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Olive oil and honey also provide natural chemicals that have demonstrated antidiabetic activity. The aforementioned plant-derived foods exert their antidiabetic activity on multiple organs (e.g., liver, intestine, pancreas, skeletal muscle, adipose tissue) and via different mechanistic pathways [ 28 , 141 , 156 , 168 ] ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Olive oil and honey also provide natural chemicals that have demonstrated antidiabetic activity. The aforementioned plant-derived foods exert their antidiabetic activity on multiple organs (e.g., liver, intestine, pancreas, skeletal muscle, adipose tissue) and via different mechanistic pathways [ 28 , 141 , 156 , 168 ] ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vast array of bioactive compounds found in medicinal plants continues to be an important resource for drug discovery and development, and structure–activity relationship (SAR) studies are important to understand how minor modifications in chemical structures can modulate antidiabetic or antioxidant activity [ 188 ]. SAR analysis has demonstrated that alkaloids found in medicinal plants such as Coptis chinensis, Commelina communis , Zingiber officinale , Nigella sativa, Cuminum cyminum , Anemarrhena asphodeloides , and Piper nigrum can improve postprandial hyperglycemia by inhibiting maltase-glucoamylase, which is becoming increasingly important as a target in antidiabetic drug discovery [ 84 , 121 , 137 , 156 , 189 ]. Such studies help researchers to design and develop compounds with improved activity and selectivity and also highlight the role of plant-based foods in the development of new drugs to control diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations